THE INFLUENCE OF GEOPOLITICAL RISKS ON STOCK PRICE CRASH WITH ESG MODERATION IN INDONESIA - Katherine, Hartati; Kim, Sung Suk (FEB Universitas Sam Ratulangi Manado, 2024)
Stock prices can indicate a company's development activity and show the investment commitment made by investors. However, under certain conditions, there is often a significant decline in stock prices which is called a market crash, such as due to geopolitical risk. This study aims to examine how geopolitical risk affects market crashes and how ESG performance is able to suppress market crashes. This study was conducted quantitatively on 64 companies with 353 observations in the period 2013-2022. Testing was carried out using panel data regression. The results of the study showed that GPR did not have a significant effect on market crashes, so ESG performance was also unable to moderate the effect of GPR on market crash risk.